The local social and environmental impacts of smallholder-based biofuel investments in Zambia - German, L.; Schoneveld, George C.; Gumbo, D.J. (2011)
High oil prices, recent commitments by industrialized countries to enhance the use of renewable energy, and efforts by developing countries to stimulate foreign investment as a pathway to development have fueled high levels of interest in the biofuel sector throughout much of sub-Saharan Africa. Zambia is no exception. A large, land-locked country with high pump prices and vast tracts of land considered by many to be “degraded” or “underutilized,” investor interest in the sector has remained high despite uncertainties associated with unproven feedstocks and market fluctuations. While investment in multiple feedstock and production models may be observed, one of the primary investments has been in jatropha outgrower schemes in which small-scale farmers grow feedstock on contract with domestic and foreign investors. We assess the history and evolution of the largest such scheme in Zambia, as well as the social and environmental impacts in two districts with large numbers of outgrowers. Findings suggest that, although such a production model may hold promise for enhancing rural livelihood benefits from the emerging biofuel sector, to date, small-scale farmers have borne the brunt of the risk and uncertainty that are the trademarks of this emerging industry. We conclude with a discussion of options to minimize forest conversion and protect farmers against high-risk investments, while harnessing the potential of this business model for enhancing rural livelihoods in Zambia and elsewhere.